Nanophotonic array-induced dynamic behavior for label-free shape-selective bacteria sieving - Shi, Yuzhi (2020)
Current particle sorting methods such as microfluidics, acoustics, and optics focus on exploiting the differences in the mass, size, refractive index, or fluorescence staining. However, there exist formidable challenges for them to sort label-free submicron particles with similar volume and refractive index yet distinct shapes. In this work, we report an optofluidic nanophotonic sawtooth array (ONSA) that generates sawtooth-like light fields through light coupling, paving the physical foundation for shape-selective sieving. Submicron particles interact with the coupled hotspots which impose different optical torques on the particles according to their shapes. Unstained S. aureus and E. coli are used as a model system to demonstrate this shape-selective sorting mechanism based on the torque-induced body dynamics, which was previously unattainable by other particle sorting technologies. More than 95% of S. aureus is retained within ONSA, while more than 97% of E. coli is removed. This nanophotonic chip offers a paradigm shift in shape-selective sorting of submicron particles and expands the boundary of optofluidics-based particle manipulation.